Roles for Hsp40 molecular chaperones in protein misfolding disease - Cyr, Douglas M. (Henry Stewart Talks, 2012)
Protein aggregation in conformational disease, The Hsp40 system, The Hsp70 system, Small oligomers, prion, yeast, Huntington's disease and protein triage, Mechanisms for proteotoxicity, Mechanisms for amyloid disease